2022
DOI: 10.1186/s40168-022-01433-6
|View full text |Cite
|
Sign up to set email alerts
|

Rice flowering improves the muscle nutrient, intestinal microbiota diversity, and liver metabolism profiles of tilapia (Oreochromis niloticus) in rice-fish symbiosis

Abstract: Background Rice-fish symbiosis, as an ecological and green aquaculture model, is an effective measure to relieve the environmental stress from intensive aquaculture. Compared with traditional aquaculture, the altered rearing pattern and environment will make differences in muscle nutrient and quality, intestinal microbiota, body metabolism, and even disease resistance in fish. Results To investigate this, we explored the differences between rice-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 43 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…Combined with the result of beta diversity analysis, the intestinal flora diversity of tilapia in the R group was higher than that in the T group, which is consistent with the previous report. 18 Further analysis of the intestinal flora composition of tilapia showed that the dominant groups of intestinal flora in the two groups were Proteobacteria, Planctomycetes, Firmicutes, Fusobacteria, Actinobacteria, Cyanobacteria, and Bacteroidetes, which is consistent with the results of previous studies. 18 In previous studies, Pseudomonas was reported to have beneficial functions such as improving plant nutrition, degrading toxic substances, producing antibiotics, and inducing systemic resistance.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Combined with the result of beta diversity analysis, the intestinal flora diversity of tilapia in the R group was higher than that in the T group, which is consistent with the previous report. 18 Further analysis of the intestinal flora composition of tilapia showed that the dominant groups of intestinal flora in the two groups were Proteobacteria, Planctomycetes, Firmicutes, Fusobacteria, Actinobacteria, Cyanobacteria, and Bacteroidetes, which is consistent with the results of previous studies. 18 In previous studies, Pseudomonas was reported to have beneficial functions such as improving plant nutrition, degrading toxic substances, producing antibiotics, and inducing systemic resistance.…”
Section: Discussionsupporting
confidence: 91%
“…Meanwhile, the growth cycle of tilapia is almost the same as that of rice, and tilapia is also a suitable farmed fish for rice-fish symbiosis. 18 In this study, we analyzed the composition of amino acids and fatty acids in the tilapia muscle from ricefish symbiosis and pond culture. We explored the structure Brevundimonas plays a positive role as beneficial gut bacteria in enhancing intestinal immunity and maintaining gut health in fish.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that interventions with beneficial substances can reshape the gut microbiota in colitis mice, leading to significant changes in certain bacterial genera [ 37 , 38 ]. In our study, we observed that compared to DSS-induced model mice, treatment with heat-killed S. boulardii increased the abundance of beneficial bacterial genera, including Dubosiella [ 39 ], Ligilactobacillus [ 40 , 41 ], Turicibacter [ 42 , 43 ], and Ileibacterium [ 44 ]. The growths of these genera were significantly suppressed in DSS model mice, indicating that heat-killed S. boulardii intervention can regulate the gut microbiota by restoring the abundance of dominant bacteria, thus achieving a new balance.…”
Section: Discussionmentioning
confidence: 99%
“…In animal intestines, the Firmicutes and Bacteroidetes phyla are dominant and play essential roles in promoting host health, boosting immunity, and maintaining homeostasis [80]. An elevated ratio of F/B is linked with some metabolic syndrome, such as obesity and chronic inflammation [81].…”
Section: The Effect Of Pros On Intestinal Microbiotamentioning
confidence: 99%